(untitled) (Balthazar, 2022)
Mario Mieli, who was an activist of the gay movement in the 70s, opened a queer track still relevant today. His criticism of patriarchal capitalism parallels a criticism of the identity and revisionists discourses endorsed by certain liberation movements. Psychoanalytic tools are instrumental in the deconstruction of the binary regiment and in the fight against the colonialism of the dissimilar.